The Burden of War and Future Generations - Pigou, A. C. (Quarterly Journal of Economics, 1919)
Burdens of war are objective and subjective, 242. — Costs resulting from destruction, and cost of maintaining the fighting forces, 243. — Choice between rival ways of financing a war, 245. — Different effects of the levy plan and the loan plan, 247. — The assumed burden of a loan to the lender, 249. — Subjective burdens of levy and loan methods, 252. — Conclusion, 254.